Carcass and meat characteristics of grass cutter (thryonomys swinderianus) (2006)
A total of twelve adult mole grass cutter (cane rats) with an average age of 38 months were used for the evaluation of meat quality attributes and carcass characteristics. The animals were starved of feed for 16 hours, weighed, stunned, slaughtered and properly bled. The thoroughly bled carcasses were scalded and eviscerated. The dressed carcass was cut into two half carcasses, one half was dissected to determine meat yield while the other half was cut into five primal cuts of leg, shoulder, rib, loin and breast, shank and flank (B. S. F.). These cuts were cooked, their percent cook yields and cooking losses were determined. Shear force value and water holding capacity (WHC) were determined. Also determined was the length to live weight ratio. Mean live weight and dressing percentage of cane rat were 4462.50g and 66.43%, respectively. Leg and the shoulder had the highest lean yield while BSF had the least (P<0.05). The larger cuts had greater cooking losses and vice-versa. An average shear force value of 2.71kg/cm(3) was obtained while a range value of 69.15- 82.10% WHC was obtained. The meat to bone ratio was highest (P<0.05) in BSF and lead in the loin. The value obtained for lain out did not differ (P> 0.05) from the values obtained for the shoulder, rib and leg. The percent cooked yield was highest in the rib cut (79:62%) and least in the leg cut (73.90%). The length to live weight ratio was 60.4, while the average carcass length was 271. 50mm.